We’ll make a town from pure nothingness - João da Cunha Borges; Rui del Pino Fernandes; Sara Silva Lopes; Teresa Marat-Mendes (Cidades, Comunidades e Território)
This paper focuses on challenge, quite typical of developing or industrializing regions, of converting a former rural settlement into a town. We analyse the urban process of Pirescoxe, a former hamlet in the riverside of Loures (Lisbon Metropolitan Region), observing the key episodes of historical formation of its current built structure, but highlighting a particularity, which was the recent conversion of elements of rural memory, built and unbuilt, into elements of cohesivity in an otherwise discrete suburban space. This analysis discloses aspects of the process of transformation of Pirescoxe over time, through its regional context, and accounting for the evolution of its typical building forms. It stems from observation of photographic and cartographic elements, historical and contemporary, as well as of the urbanization plans that transformed this space. The conclusion notes how the most decisive intervention in Pirescoxe was the one that more strongly emphasized the ruins of the rural past as elements of memory and identity.